Scripts and Medical Scripture in Vietnam: Nôm and Classical Chinese in the Historic Transmission of Medical Knowledge in Pre-Twentieth Century Vietnam - Thompson, C Michele (Nghiên cứu Chữ Nôm (Research on Nôm Script), 2006)
Keywords: dept.his

Book Review: Beyond the Bronze Pillars: Envoy Poetry and the Sino-Vietnamese Relationship (review) - Thompson, Claudia Michele (China Review International, 2006)
Keywords: book.review; dept.his

American Social Credit Movement. - Kalk, Bruce H. (2006)
Keywords: dept.his; faculty_collection; sabbatical_report

Rethinking Friedrich Meinecke's historicism - Paddock, Troy R. E. (Rethinking History, 2006)
This essay revisits the work of the German historian Friedrich Meinecke and offers new interpretation of his major works, Weltbürgertum und Nationalstaat (1907), Die Ideen der Staatsräson in der neuen Geschichte (1924), and Die Entstehung des Historismus (1936). The standard interpretation of Meinecke's work maintains that World War I caused a break in his thinking and caused him to rethink the role of power in the state. By stressing the first half of Weltbürgertum rather than the second, this article delineates a continuity of Meinecke's thought and points to the limitations of historicism as a historical narrative. It offers a possible explanation for how the conservative implications in the thought of an individual, who personally and politically was a Vernuftrepublikaner, could escape the author himself. This article also discusses what could be called the classical liberal critique of Meinecke's historicism, points to some of its limitations, and offers a more measured criticism of Meinecke that examines him on his own terms—and finds him wanting.
Keywords: Classical liberalism; Historicism; Historiography; Meinecke; Natural law; State; dept.his

Chronoscapes/chronos escapes: a meditation on historical time - Paddock, Troy R. E. (Ecoscapes: geographical patternings of relations, 2006)
Keywords: dept.his

'Truth Systematised’: The Changing Debate over Slavery and Abolition - Forbes, Robert P. (Prophets of Protest: Reconsidering the History of American Abolitionism, 2006)
The first collection of original contributions on American abolitionism to appear in a generation.The campaign to abolish slavery in the United States was the most powerful and effective social movement of the nineteenth century and has served as a recurring source of inspiration for every subsequent struggle against injustice. But the abolitionist story has traditionally focused on the evangelical impulses of white, male, middle-class reformers, obscuring the contributions of many African Americans, women, and others.Prophets of Protest, the first collection of writings on abolitionism in more than a generation, draws on an immense new body of research in African American studies, literature, art history, film, law, women's studies, and other disciplines. The book incorporates new thinking on such topics as the role of early black newspapers, anti-slavery poetry, and abolitionists in film and provides new perspectives on familiar figures such as Sojourner Truth, Louisa May Alcott, Frederick Douglass, and John Brown.With contributions from the leading scholars in the field, Prophets of Protest is a long overdue update of one of the central reform movements in America's history.
Keywords: dept.his

Beasts of the field: A narrative history of California farmworkers, 1769-1913 - Rondinone, Troy (Labor History, 2006)
Keywords: dept.his; ⛔ No DOI found

Wilhelminism and its legacies: German modernities, imperialism and the meanings of reform, 1890-1930. - Paddock, T (German Studies Review, 2006)
Keywords: dept.his; ⛔ No DOI found

Democratic discourses: the radical abolition movement and antebellum american literature - Davis, Hugh (The Journal of American History, 2006)
Keywords: dept.his; peer-reviewed

On the provenance of the holy shroud of Lirey/Turin: A minor suggestion - Friedlander, Alan (The Journal of Ecclesiastical History, 2006)
Keywords: dept.his

Creating an oriental feindbild - Paddock, Troy (Central European History, 2006)
Keywords: dept.his

Review of Ceramic technology, part XII of chemistry and chemical technology - Thompson, C. Michele (History and Philosophy of the Life Sciences, 2006)
Keywords: book.review; dept.his; ⛔ No DOI found